ANALISA PERMINTAAN PARKIR DI STASIUN PONCOL DAN TAWANG SEMARANG - Sutarto, Agung (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract: Activities in a railway station will generate trips which need parking space. This research is aimedÃÂ  to analyzeÃÂ  the difference demand characteristics between Poncol and Tawang stations. TheseÃÂ  characteristicsÃÂ  areÃÂ  theÃÂ  effectÃÂ  ofÃÂ  ticketÃÂ  priceÃÂ  toÃÂ  tripÃÂ  attraction,ÃÂ  tripÃÂ  attractionÃÂ  model, transportation mode demand and parking space demand. The economic class and transportation of goodsÃÂ  areÃÂ  servedÃÂ  inÃÂ  Poncol.ÃÂ  BussinessÃÂ  andÃÂ  executiveÃÂ  classÃÂ  isÃÂ  servedÃÂ  inÃÂ  TawangÃÂ  stastion.ÃÂ  The correlationÃÂ  betweenÃÂ  tripÃÂ  attractionÃÂ  andÃÂ  theÃÂ  numberÃÂ  ofÃÂ  ticketÃÂ  canÃÂ  beÃÂ  describedÃÂ  inÃÂ  theÃÂ  following equationÃÂ  : YtripÃÂ  attractionÃÂ  =ÃÂ  120,51ÃÂ  +ÃÂ  1,0602 XticketÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  for PoncolÃÂ  station,ÃÂ  andÃÂ  : YtripÃÂ  attractionÃÂ  =ÃÂ  175,21 + 1,3212 XticketÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  for Tawang station. Correlation betweenÃÂ  trip attraction andÃÂ  transportation mode can be describedÃÂ  inÃÂ  theÃÂ  following equationÃÂ  : Ytripattr = 7,3063 + 3,271 XprivateÃÂ  car + 2,464 Xbecak + 2,406 Xmotor cycle + 2,448 Xpick upÃÂ ÃÂ  for Poncol,ÃÂ  and : Ytrip attractionÃÂ ÃÂ  =ÃÂ  4,467 + 3,567 Xprivate car + 2,517 Xmotorcycle,ÃÂ  for Tawang station. It can be concluded that the parking space demand for each passenger isÃÂ  1,48 m2ÃÂ  in Poncol station and 7,3 m2ÃÂ  in Tawang station. Trips attraction perÃÂ  ticketÃÂ ÃÂ ÃÂ  is 1,0602ÃÂ  in Poncol stationÃÂ  andÃÂ  1,3212ÃÂ  inÃÂ  TawangÃÂ  station.ÃÂ  Transportation mode whichÃÂ  isÃÂ  dominantlyÃÂ  usedÃÂ  in Poncol stationÃÂ  isÃÂ ÃÂ  motorcycle, whileÃÂ  in Tawang stationÃÂ  is private car and motorcycle. Private carÃÂ  is often used because the public transport facility could not support the train passengerÃ¢â¬â¢s needs. There are variableÃÂ  pick-upÃÂ  vehiclesÃÂ  in PoncolÃÂ  because PoncolÃÂ  stationÃÂ  servedÃÂ  passengersÃÂ  andÃÂ  goods. SRP which are used in Poncol station for passenger carÃÂ  65 SRP, motorcycle 282 SRP, pick-up 52 SRP, andÃÂ  tricycle (becak) 64 SRP.ÃÂ ÃÂ  SRP which are usedÃÂ  in Tawang station for passenger car 235 SRP, motor cycle 350 SRP and tricycle (becak) 13 SRP. Keywords:ÃÂ  trips attraction,ÃÂ  parking demand,ÃÂ  poncol station,ÃÂ  tawang station . ÃÂ  Abstrak: Kegiatan di stasiun kereta api akan menghasilkan perjalanan yang membutuhkanÃÂ  ruang parkir. PenelitianÃÂ  iniÃÂ  bertujuanÃÂ  untukÃÂ  menganalisisÃÂ  karakteristikÃÂ  permintaanÃÂ  perbedaanÃÂ  antara stasiunÃÂ  PoncolÃÂ  danÃÂ  Tawang. CiriÃÂ  iniÃÂ  pengaruhÃÂ  hargaÃÂ  tiketÃÂ  keÃÂ  atraksiÃÂ  perjalanan,ÃÂ  modelÃÂ  tarikan perjalanan,ÃÂ  kebutuhanÃÂ  transportasiÃÂ  modeÃÂ  danÃÂ  kebutuhanÃÂ  ruangÃÂ  parkir. KelasÃÂ  ekonomiÃÂ  dan transportasiÃÂ  barangÃÂ  disajikanÃÂ  diÃÂ  Poncol.BisnisÃÂ  danÃÂ  kelasÃÂ  eksekutifÃÂ  disajikanÃÂ  diÃÂ  Tawang stastion. KorelasiÃÂ  antaraÃÂ  dayaÃÂ  tarikÃÂ  perjalananÃÂ  danÃÂ  jumlahÃÂ  tiketÃÂ  dapatÃÂ  digambarkanÃÂ  dalam persamaanÃÂ  berikut: YtripÃÂ  atraksi =ÃÂ  120,51ÃÂ  +ÃÂ  1,0602 XticketÃÂ  untukÃÂ  stasiun Poncol, dan: YtripÃÂ  atraksi = 175,21ÃÂ  +ÃÂ  1,3212ÃÂ  XticketÃÂ  untukÃÂ  stasiunÃÂ  Tawang. KorelasiÃÂ  antaraÃÂ  dayaÃÂ  tarikÃÂ  dan modaÃÂ  transportasi dapat digambarkan dalam persamaan berikut: Ytarikan = 7,3063 + 3271 Xmobil pribadi + 2.464 Xbecak + 2.406 XsepedaÃÂ  motorÃÂ  +ÃÂ  2.448 Xpick-upÃÂ  untukÃÂ  stasiun Poncol,ÃÂ  dan: YtarikanÃÂ  =ÃÂ  4467ÃÂ  +ÃÂ  3567 XmobilÃÂ  pribadiÃÂ  + 2.517 XsepedaÃÂ  motor,ÃÂ  untukÃÂ  stasiunÃÂ  Tawang. DapatÃÂ  disimpulkanÃÂ  bahwaÃÂ  ruangÃÂ  parkirÃÂ  permintaan penumpang masing-masing 1,48 mÃÂ² di stasiun Poncol dan 7,3 mÃÂ² di stasiun Tawang. Perjalanan atraksi perÃÂ  tiket di stasiun Poncol 1,0602 dan 1,3212 di stasiun Tawang.Transportasi modus yang dominan digunakan di stasiun Poncol adalah sepeda motor, sedangkan di stasiun Tawang adalah mobil pribadi dan sepeda motor. mobil pribadi sering digunakan karena fasilitas transportasi publik tidak dapat mendukung kebutuhan penumpang kereta. Ada variabel kendaraan pick-up di stasiun PoncolÃÂ  PoncolÃÂ  karenaÃÂ  melayaniÃÂ  penumpangÃÂ  danÃÂ  barang. SRPÃÂ  yangÃÂ  digunakanÃÂ  dalamÃÂ  stasiun Poncol untuk penumpang mobil 65 SRP, sepeda motor 282 SRP, pick-up 52 SRP, danÃÂ  rodaÃÂ  tiga (becak) 64 SRP. SRP yang digunakan dalam stasiun Tawang untuk mobil penumpang 235 SRP, sepeda motor 350 SRP dan roda tiga (becak) 13 SRP Kata kunci: bangkitan perjalanan, kebutuhan parkir, stasiun poncol, stasiun tawang